Methodological foundations forming of organizational structures based on a systemic approach - Rud , K. (Ways to Improve Construction Efficiency, 2023)
The article makes a scientific research of existing methodological approaches that have been formed in management. The article also analyses the causes of the collapse of investment projects, in particular in the construction industry, which threaten the stability of the functioning of national economies. All these researches give an opportunity to find the real causes of ineffective implementation of projects. The author offers a methodological approach to the formation of a holistic organizational structure of the socio–economic system, which has the goal to solve the problem of crisis phenomens in management. The author`s approach gives an opportunity to form organizational structure in an organic combination with the economic processes that take place in it and provide the qualitative formation of the organizational structure, which makes it possible to make control over each of its economic elements and ensure an absolutely effective management. Based on a systemic approach, the author considers the organizational structure as a dynamic system that consists from economic elements which necessary for the effective implementation of the purpose of the created structure. This approach to considering the organizational structure is different from the traditional one, in which the structure of the organization is a static system, the elements of which are only labor resources with defined functions. Consideration of the organizational structure as an integral system that consists from selected homogeneous economic elements which structure on the basis of normative model in which the management and managed subsystems are allocated, and also there are the main, auxiliary and service production in the managed subsystem gives an opportunity to form a normative model of the organizational structure which provides qualitative structuring of all its elements.